Avaliação da utilização do glifosato para manejo de macrófitas aquáticas - Marina Andrada Maria (2017)
The possibility of using herbicides in aquatic ecosystems to control macrophytes in unbalanced conditions led to the need for studies that evaluate the efficiency and environmental impacts of this use. Glyphosate is one of the major active ingredients used worldwide as an herbicide and is known for its effectiveness, broad spectrum of action and low toxicity. In order to understand and evaluate the effect of the use of an herbicide on the macrophytes, as well as their impact and changes in the aquatic ecosystem, benchtop studies and pond environments microcosms were carried out. The experiments were conducted using their commercial formulation, Roundup Original®, for the control of macrophytes Eichhornia crassipes and Salvinia sp. The evaluated doses were from 6.25 to 100 L.ha-1 only the latter showed a significant difference of effect, compared to the control, preventing regrowth and with low residual effect for the two species studied. Glyphosate in natural samples has a short half-life, ranging from 3.6 to 7.3 days, suffering reduction even in refrigerated or frozen samples, and it can be stored, for quantification purpose, for a maximum of four days. Glyphosate causes changes in the pH and conductivity parameters and increase in the concentration of chloride, nitrate and sulfate anions in the water. When evaluated individually in solution, the toxicity of glyphosate, AMPA, Roundup and Iharaguens® surfactant standard is high; however, the microcosm samples showed no toxicity and the absence of abnormal behaviors or results in the ecosystem evaluation. The effects on the non-target organisms were subtle, without great ecological relevance. There was no significant difference for heterotrophic bacteria, only indications of a possible selection of glyphosate degrading strain. The phytoplankton and the periphyton had a reduction in species richness and diversity and increase of the density of organisms, but not significant. There were also changes in the relative abundance of the families of the species. The active ingredient had a chronic risk quotient of 0.66 and acute of 0.52 for microcrustaceans, which compared to the risk assumption does not compromise the area and the conditions evaluated. The commercial formulation had a chronic risk quotient of 5.06 and an acute risk of 2.02, which indicates an environmental risk, however, the toxicity absence of water samples from the microcosms showed that there is no environmental risk in the assessed condition of application. Toxic effects were identified in direct applications in water without macrophyte coverage